On the female gonocoxites of Asian, Arabian, and African Clivinini with realignment of the Thliboclivina-, Physoclivina-, and Eoclivina-species groups, and notes on the higher systematics of the tribe Clivinini Rafinesque, 1815 (Coleoptera, Carabidae) - Balkenohl, Michael (Zootaxa, 2022)
Out of the Oriental, Arabian, and African Clivinini, the external female reproductive tracts of 32 genera and subgenera were investigated. Five different basic morphologies were found and within the basic plans, genus-specific variations. The data are compared with the current systematics of the Clivinini at a suprageneric level with focus on the Asian groups. One of the morphologies is completely unknown for Scaritinae. The sixteen species concerned are investigated in more detail and belong to the genus Thliboclivina Kult, the two subgenera Physoclivina Kult and Eoclivina Kult, and the Oriental Clivina attenuata-species group. For these groups, the new subtribe Thliboclivinina subtr. nov. is erected. This arrangement is based on the conspicuous and unique morphology of the female gonocoxite and epipleurite corresponding to several external characters, which are as well unique among the Clivinini. Ecological data support this arrangement. The subgenera Physoclivina and Eoclivina are elevated to genus level (stat. nov.); for the Oriental C. attenuata-species group, the genus Sulciclivina gen. nov. is described. An identification key to the four genera of the subtribe Thliboclivinina subtr. nov. is provided. For Asian, Arabian, and African Clivinini, an overview of the basic shapes of the external female genitalia is provided in the form of examples in a picture catalogue. The species Clivina svenssoni Basilewsky is arranged into the genus Ancus Putzeys (stat. nov.).